Exploring the Challenges Faced by Small Insurance Brokers in Achieving Sustainable Growth: A Case Study in Botswana's Insurance Industry - Maalila Malambo (IJEBD (International Journal of Entrepreneurship and Business Development))
Purpose: This study assesses the challenges faced by small insurance brokers in Botswana, focusing on regulatory dynamics, market conditions, financial constraints, technological disparities, consumer preferences, marketing limitations, distribution challenges, service constraints, and training needs.